Health Care for Sexual and Gender Minority Adolescents: scoping review (Research, Society and Development, 2022)
Objective: To map scientific evidence on health care for adolescents from sexual and gender minorities in the context of primary care. Methodology: Scoping Review, which was developed based on the recommendations of the Joanna Briggs Institute Reviewers international guide. A search was carried out in selected databases that contained full articles and answered the question: what would be the knowledge or scientific evidence that could guide the development of protocols and educational actions in the context of primary health care? Searches were performed in six international and national databases, on works published until 2021. Results: Among the 394 studies, 25 were selected for full reading with a final sample of 11 studies. The 11 studies were published from 2017 to 2020. The selected studies are of international scope and have a quantitative, qualitative and qualiquantitative approach. The studies brought important proposals for interventions that can be carried out to improve the care provided by professionals in the primary care environment. Conclusion: It is noticed that the field of study is little explored in the national literature and studies are observational, with a gap in relation to the diversity of care for sexual and gender minorities that should be filled by future studies.